CRYSTALLINE AND HETEROCYCLYC AROMATIC COMPOUNDS IN GEORGIAN PETROLEUM - Natela Khetsuriani; Vladimer Tsitsishvili; Elza Topuria; Irina Mchedlishvili; Zaza Molodinashvili (World Science, 2021)
The individual composition of polycyclic aromatic hydrocarbons has been studied in high boiling (340–590°) fractions of Norio oil (wells 200, 201) which are characterized by high content of aromatic hydrocarbons and high intensity fluorescence. The eluates obtained by adsorption fractionation of aromatic hydrocarbons separated by aniline and concentrates of their crystalline components have been studied by GC, MS and GC-MS methods. For analysis of the obtained data an automated system of mass deconvolution and identification (AMDIS) was used. In the eluates under investigation the following structures were identified: indenes, tetralines, dinaphtilbenzenes, naphthalenes, fluorenes, phenantrenes, antracenes, mono- and polyalkyl derivatives ofnaphtofluorene and phenantrene, and terpeniles. In crystal samples of the eluates the banzantracene, chrizene, their methyl-, dimethyl and trymethylanaloges, phenantrene derivatives, antracenes and pyrenes were identified. The heterocyclic analogues of polycyclic aromatic hydrocarbons likemethylbenzoanthracenes, benzonaphthothiophenes, benzocarbazoles and dibenzthiophene were identified in Georgian oils for the first time.